2020
DOI: 10.3390/met10020166
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Corrosion Resistance of Biomedical Zr-Ti Alloys Using a Thermal Oxidation Treatment

Abstract: Binary Zr-Ti alloys spontaneously develop a tenacious and compact oxide layer when their fresh surface is exposed either to air or to aqueous environments. Electrochemical impedance spectroscopy (EIS) analysis of Zr-45Ti, Zr-25Ti, and Zr-5Ti exposed to simulated physiological solutions at 37 °C evidences the formation of a non-sealing bilayer oxide film that accounts for the corrosion resistance of the materials. Unfortunately, these oxide layers may undergo breakdown and stable pitting corrosion regimes at an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…5 presents the surface topography of Ti-20Zr alloy and it reveals the influence of simulated body fluid on the surface of the sample. Can be seen that the passive layer has an external porous film [7,8] which is suitable for oseoinduction growth of the bone. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5 presents the surface topography of Ti-20Zr alloy and it reveals the influence of simulated body fluid on the surface of the sample. Can be seen that the passive layer has an external porous film [7,8] which is suitable for oseoinduction growth of the bone. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7-8). Another study regarding the corrosion resistance of Zr−Ti alloys shows too that the thermal oxidation in air at 500 • C does improve the corrosion resistance and suggests that prior to the use of such alloys as implant materials, a treatment consisting of thermal oxidation in air followed by exposure to a physiological solution should be applied [105].…”
Section: Surface Chemistrymentioning
confidence: 99%
“…It was found out that the alloys possess increased biocompatibility compared to cpTi, proving that they are a great candidate for small-diameter implants. Alternate outcomes were revealed during the examination of the electrochemical behavior of the alloys with titanium and zirconium [16,17]. These studies showed that the alloy passivated more easily in Ringer solution compared to cpTi, having a more stable passive film than Ti [18,19].…”
Section: Introductionmentioning
confidence: 99%